2017
DOI: 10.1002/pld3.16
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide binding analysis of AtGNC and AtCGA1 demonstrates their cross‐regulation and common and specific functions

Abstract: GATA transcription factors are involved in multiple processes in plant growth and development. Two GATA factors, NITRATE-INDUCIBLE, CARBON METABOLISM-INVOLVED (GNC) and CYTOKININ-RESPONSIVE GATA FACTOR 1 (CGA1, also named GNL), are important regulators in greening, flowering, senescence, and hormone signaling. However, their direct target genes related to these biological processes are poorly characterized. Here, GNC and CGA1 are shown to be transcription activators and by using chromatin immunoprecipitation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Similar results 351 were observed when examining for the enrichment of the GATC-binding motif in the same 352 dataset. Prior studies suggest an autoregulatory role with members of the GNC family serving to 353 inhibit their own expression (Richter et al, 2010;Ranftl et al, 2016;Xu et al, 2017). We 354 identified GNC binding sites by ChIP-Seq in the promoters of GNC and CGA1, consistent with 355 direct inhibitory regulation, and confirmed that expression of both CGA1 and the native GNC 356 gene is inhibited in the 35S:GNC lines (Fig 5J, K).…”
Section: Pbm 345supporting
confidence: 66%
See 1 more Smart Citation
“…Similar results 351 were observed when examining for the enrichment of the GATC-binding motif in the same 352 dataset. Prior studies suggest an autoregulatory role with members of the GNC family serving to 353 inhibit their own expression (Richter et al, 2010;Ranftl et al, 2016;Xu et al, 2017). We 354 identified GNC binding sites by ChIP-Seq in the promoters of GNC and CGA1, consistent with 355 direct inhibitory regulation, and confirmed that expression of both CGA1 and the native GNC 356 gene is inhibited in the 35S:GNC lines (Fig 5J, K).…”
Section: Pbm 345supporting
confidence: 66%
“…9A). Prior studies have generally assumed that GNC will serve as 484 an activator, this informing the search for target genes (Hudson et al, 2011;Klermund et al, 485 2016;Xu et al, 2017), although a repressive function in the control of SOC1 for flowering time 486 was uncovered (Richter et al, 2013a). Even though the evidence suggests that GNC primarily 487 functions as a repressor, this does not preclude its functioning in some instances as a 488 transcriptional activator as we confirm that induction of GNC stimulates expression of the target 489 gene SPCH, consistent with a prior study .…”
Section: But Based 477mentioning
confidence: 99%
“…GNC and GNL bind the GATA motif in the GLU1 promoter (Hudson et al, 2011), whereas the tobacco GATA TF, AGP1, activates NtMYC2 by binding to the GATC motif in the NtMYC2 promoter (Sugimoto et al, 2003). Moreover, genome-wide binding analysis of GNC and GNL reveals that both GATA and GATC ciselements are enriched in the targets (Xu et al, 2017). We identified multiple GATA and GATC cis-elements in the promoters of DAT, D4H, T3R, T3O, and T16H2.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have demonstrated that GATA TFs bind to both GATA and GATC motifs (Newton et al, 2001;Sugimoto et al, 2003;Xu et al, 2017). The D4H promoter, highly activated by CrGATA1 (Fig.…”
Section: The Gatc Motif Is Crucial For Crgata1 Activation Of the D4h mentioning
confidence: 84%
See 1 more Smart Citation